Detection Of Homozygous Haemoglobin Constant Spring By Capillary Electrophoresis Method - Raja-Zahratul Azma,; Khamisah M-Gaus ,; Suria A-Aziz ,; Hafiza Alauddin ,; Azlin Ithnin ,; Noor-Farisah Razak ,; Nor-Hidayati Sardi ,; Malisa Mohd-Yusoff ,; Zarina A-Latiff ,; Hamidah Alias ,; Endom Ismail ,; Danny Koh-Xuan-Rong; et al. (ARC Publications, 2024)
Introduction: Hemoglobin Constant Spring (HbCS) is often missed due to almost normal red cells indices and is present at a low level in peripheral blood. However, analysis of blood samples using capillary electrophoresis (CE) is able to differentiate between heterozygous and homozygous state of HbCS. Methods: An eight-year-old Malay girl presented with severe anaemia and hepatosplenomegaly following a viral infection. The diagnosis of homozygous HbCS was made from Hb analysis by CE which showed a small peak (5.3%) at Hb CS zone. His brother had similar CE findings while both of her father and mother showed much smaller peaks (0.7% and 0.4% respectively) at similar zone which were consistent with heterozygous HbCS. All findings were confirmed by few molecular analysis techniques. Conclusion: This case highlights the importance of detection of homozygous HbCS by CE. CE is useful as a fast screening method for detection of HbCS in hematology laboratory where molecular analysis is not available and patient with homozygous HbCS has higher risk to develope acute hemolysis when having infection. Keywords: Capillary electrophoresis, Hb Constant Spring, Homozygous state.